Genomic Profile of OsCOMT in Indonesian Purple Rice - Wijayanti, Ernanin Dyah; Safitri, Anna; Siswanto, Dian; Fatchiyah, Fatchiyah (Universitas Brawijaya, 2022)
The Indonesian purple rice (IPR), a crossbreeding of black and white rice, is a potential source of ferulic acid. Up to this point, the genomic similarity between the crossbreeding and its parentals has not been determined, particularly in genes involved in ferulic acid biosynthesis. In this present work, we analysed the profile of Oryza sativa caffeic acid-O-methyltransferase (OsCOMT) gene in IPR. The genomic DNA was extracted by CTAB method, then amplified with a specific primer of OsCOMT gene. The amplicon was sequenced by Sanger method and confirmed by geneID NC_029259.1. The IPR showed an amplicon of 708 bp sequence of the OsCOMT gene, indicating the gene involved in ferulic acid biosynthesis. The IPR gene profile is similar to the parentals, but there are variations in point mutations that distinguish it from the parentals. Aspartic acid was changed to Glutamine by mutations at positions 52, 69, and 79. We suggest that IPR has a novel OsCOMT gene variant that is unique as it is the crossbreed.